Omalizumab in the treatment of chronic spontaneous urticaria – literature review and own experience - Dawicka, Joanna; Wilkowska, Aleksandra; Grubska-Suchanek, Elżbieta; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2016)
Chronic urticaria is a condition characterized by the appearance of wheals and/or angioedema that last for at least 6 weeks. According to the recent recommendations, if H1-antihistamines used in four times licensed doses remain ineffective, add-on treatment with omalizumab, cyclosporine A or montelukast should be applied. This paper offers a literature review of the studies on using omalizumab in chronic spontaneous urticaria (CSU) treatment. Moreover, it presents our own experience with the use of omalizumab in the treatment of two patients with CSU. Both patients were treated with H1-antihistamines in four times licensed doses recommended by European guidelines, oral corticosteroids, montelukast, and methotrexate – all without satisfactory results. During the time of the omalizumab therapy both patients achieved a significant improvement measured by the decrease in the Average Urticaria Activity Score for 7 days (UAS7) – the first patient from 34 to 11.8 points, the second one from 41 to 5.76.